(untitled) (Physical Education, Health and Social Sciences, 2026)
This research paper examines translanguaging, code-switching and the development of Pakistani English as central issues in contemporary English linguistics. It responds to the need for linguistics research that treats Pakistani learners and speakers not as deficient users of English but as multilingual meaning-makers working across Urdu, Sindhi, regional languages and English. The paper adopts a qualitative, corpus-informed documentary design. It synthesizes recent policy reports, learning assessments and scholarly studies with classical theories of World Englishes, translanguaging and corpus linguistics. The study proposes a Multilingual Ecological Corpus Framework that connects macro language policy, meso-level educational practice and micro-level linguistic patterns such as lexical borrowing, code-switching, article variation, prepositional choices and subject-verb agreement. The analysis shows that English in Pakistan is shaped by three simultaneous forces: the institutional pressure of standard English, the local identity value of Pakistani English and the practical classroom need for multilingual support. Evidence from Pakistan-based reports shows that English remains an important educational and socioeconomic resource, yet achievement gaps remain serious, especially in public-sector contexts. International studies on World Englishes and translanguaging support the argument that multilingual language use should be studied as systematic, purposeful and context-sensitive. The paper concludes that English linguistics in Pakistan should move beyond error-only descriptions and adopt a balanced model that distinguishes communicative innovation from forms requiring academic intervention. The study contributes a new idea: corpus-informed translanguaging pedagogy, which uses local bilingual examples to teach standard academic English without denying Pakistani English identity. This approach can support research, teacher education and language-policy development in multilingual Pakistan. for multilingual classrooms in Pakistan and comparable settings.